Efektivitas Pengambilan Keputusan Aliansi Strategis Dalam Menciptakan Keunggulan Kompetitif Bagi Perusahaan - Yosinta Damayanti (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2022)
The era of globalization along with the COVID-19 pandemic brings more challenges for companies to survive in facing their competition. Competitive advantage is the main capital that must be owned by the company that is facing its competition. In an effort to create a competitive advantage, leaders always strive to take the company through the right steps, one of which can be through decision-making in the form of strategic alliances. The purpose of the study is to develop scientific insights regarding the effectiveness of strategic alliance decision-making in creating a competitive advantage for the company. the method used in this study is using qualitative research methods in the form of literature study. The results of this study indicate that strategic alliance decision-making is a form of strategy that is able to create a competitive advantage for the company.